Haemodynamics in Different Flow Lumen Configurations of Customised Aortic Repair for Infrarenal Aortic Aneurysms. (May 2019) - Overeem, Simon P.; de Vries, Jean-Paul P.M.; Boersen, Jorrit T.; Slump, Cornelis H.; Reijnen, Michel M.P.J.; Versluis, Michel; Groot Jebbink, Erik
Abstract : Objective: Customised aortic repair (CAR) is a new and minimally invasive technique for the endovascular treatment of abdominal aortic aneurysms (AAAs). The aneurysm is completely sealed with a non-contained, non-cross linked polymer, while a new flow lumen is created with balloons. For CAR, the haemodynamically most favourable balloon and flow lumen configuration has not been established before; therefore, four flow parameters were assessed in an in vitro model. Methods: Three in vitro balloon configurations were implanted in an in vitro AAA model; a configuration with crossing balloons (CC) and two parallel configurations (PC1 and PC2). These three models were consecutively placed in a flow system that mimics physiological flow conditions. Laser particle imaging velocimetry (PIV) was used to resolve spatial and temporal flow patterns during the cardiac cycle. In house built algorithms were used to analyse the PIV data for the computing of (i) flow velocity; (ii) vorticity; (iii) wall shear stress (WSS); and (iv) time averaged wall shear stress (TAWSS). Results: Suprarenal flow patterns were similar in all models. The CC showed a higher infrarenal velocity than PC1 and PC2 (38 cm/s vs. 23 cm/s vs. 23 cm/s), and a higher vorticity at the crossing of the lumens (CC: 337/s; PC1 127/s; PC2: 112/s). The lowest vorticity was observed in PC2, especially in the infrarenal neck (CC: 200/s; PC1 164/s; PC2: 98/s). Although WSS and TAWSS varied between configurations, values were in the within non-pathological range. Conclusion: The flow lumens created by three balloon configurations used in an in vitro model of CAR have been studied, and resulted in different haemodynamics. The differences in velocity and lower vorticity, especially at the crossing section of the two balloons, showed that PC2 has favourable haemodynamics compared with the CC and PC1. Future research will be focused on the clinical applicability of CAR based on the PC2 design.